Uji Efek Nefroprotektif Ekstrak Etanol Daun Kari (Murraya Koenigii (L.) Spreng) Terhadap Kadar Blood Urea Nitrogen (BUN) Dan Kreatinin Tikus Putih Jantan Galur Wistar (Rattus Norvegicus) Yang Diinduksi Doksorubisin - Yuziani Yuziani; Arvinnia Tanida Harefa; Khairunnisa Z (Pusat riset dan Inovasi Nasional, 2023)
Cancer is one of the leading causes of death in the world. A highly-effective therapy in cancer is chemotherapy using doxorubicin. Sustainable doxorubicin usage could damage the kidneys due to Reactive Oxygen Species (ROS) formation that could be seen by increased levels of BUN and creatinine. Curry leaves are commonly found in Aceh and has high antioxidant rate so it has the potential to suppress kidney damage due to the use of doxorubicin. These antioxidants could be useful for decreasing levels of BUN and creatinine. The purpose of this research is to test the nephroprotective effect of Ethanol Extract of Curry Leaves (EECL) to prevent kidney failure on doxorubicin induced wistar strain male white rats. The method of this research is experimental with post test only control group design. The number of samples used was 25 rats which were divided into 5 groups. Positive control group (given vitamin E), negative control group (given CMC-Na 0,5%), and treatment groups (given EECL at doses 50 mg/kgBB, 100 mg/kgBB, and 200 mg/kgBB) orally for 7 days straight and doxorubicin 15 mg/kgBB was induced on the 8th day. The results show that the BUN levels in the treatment group given EECL at doses 50 mg/ kgBB and 100 mg/kgBB are close to the positive control group, but the creatinine levels are still significantly different. Meanwhile, the treatment group that was given EECL at dose 200 mg/kgBB, both BUN and creatinine levels, are close to the positive control group. The conclusion of this study is that EECL has a nephroprotective effect on doxorubicin induced rats and the most effective dose is 200 mg/kgBB.